Molecular cytogenetic analysis of low-grade B-cell neoplasias: a comparative genomic hybridization study - Werner, Claudius Alexander; Döhner, Hartmut; Barth, T. F. E.; Stilgenbauer, Stephan; Plesch, Anja; Lichter, Peter; Bentz, Martin (Advances in hematopoietic stem cell transplantation and molecular therapy, 1998)
Malignant tumors are characterized by deregulation of cell proliferation and differentiation, often induced by genomic alterations within the tumor cells (see Fischer et al., this volume). In acute leukemias, chromosomal banding analyses have greatly contributed to our understanding of key mechanisms in leukemogenesis. One important example is the identification of protooncogenes, such as MLL, ETO, AML 1, or TEL, which are activated by recurrent chromosomal translocations. In addition, specific chromosomal aberrations are closely associated with the phenotype of the tumor cells and even clinical features such as response to therapy and the probability of long-term survival (Pui 1995).